Serve analysis of professional players in beach volleyball - Jimenez-Olmedo, J. M.; Penichet-Tomás, A.; Saiz-Colomina, S.; Martinez-Carbonell, J. A.; Jove-Tossi, M. A. (Journal of Human Sport & Exercise, 2012)
This study has been developed for the European Beach Volleyball Championship in 2005. The video-recorded analysis was held using Sportcode Pro v.8.5.2 software. The aim of study was to determine the types of serve used, depending on the time of the set in which they occur. Quantitative analysis with a sample of 10 players that make up 5 teams with a total of four meetings with a total of 327 serves analyzed. The serves were classified depending on the period which they occurred, the period being 1 (items 1 to 7), period 2 (from point 8 to 14) and period 3 (point 15 to 21). he statistical analysis was conducted using the statistical software SPSS 19, Chi-square test established significant differences between the different types of serve for period 1 and 2 (p<0.05), but no significant differences were established in the period 3 to floating serve and power jump (p>0.05). The results showed a decrease of using a serve with jump power at period 1 (89.7%) compared to the period 3 (27.3%), while the floating and floating serve jump respectively increase at period 1 (6.3% -4%) in the period 3 (23.4% -49.4%).